Inicjatywa obywatelska w praktyce politycznej III RP - Piasecki, Andrzej (In Gremium. Studies in History, Culture and Politics, 2009)
Civil initiative in the political experience in the Third Republic of Poland This article is devoted to the description of the functioning of direct democracy mechanisms provided for in the political system of the Third Republic of Poland. The author concentrates mostły on the definitional consideration referring to the institution of civil initiative (public). Later, the author carries out an anałysis of the implementation process of this form of direct democracy in the Polish legal system, which was initiated in local communities.